Nutritional thermal ecology: investigating the combined influence of temperature and nutrient availability on plant‐ectotherm trophic interactions - Meunier, Cédric L. (2024)
Many primary consumers in freshwater, marine and terrestrial systems are ectotherms(e.g. zooplankton and insects), whose metabolisms, and therefore nutritional demands,are modulated by temperature. Further, nutrient availability largely influences the quality of resources consumed by these organisms, and hence affects whether nutritionaldemands of consumers are fulfilled. From these considerations, a crucial questionarises: how do temperature and nutrient availability together modulate trophodynamics at the basis of food webs? Addressing this question for zooplankton and insects isessential since these consumers are the most abundant metazoans on Earth, and theylink primary production to higher trophic levels. Here, we synthesize the existing literature and offer avenues to guide future scientific endeavours. We highlight that the vastmajority of studies on the combined influence of temperature and nutrient availabilitypublished to date focus on at least one of the following research topics: 1) metabolicrequirements of ectotherms; 2) feeding behaviour; 3) eco-evolutionary processes; and4) trophodynamics. We pose that further advances in this field of research may provide a robust understanding of how modulations of consumer metabolic requirementsand resource quality define consumer–producer interactions across marine, freshwaterand terrestrial ecosystems. This research effort would enable to combine the fields ofEcological stoichiometry and of Metabolic theory of ecology, and create an integratedapproach, which we propose to call Nutritional thermal ecology.